"3D-PP": three-dimensional visual programming system - Oshiba, T.; Tanaka, J. (IEEE workshop on visual languages, 1999)
We are interested in three-dimensional visual programming environments in particular. The conventional visual programming systems mainly focuses on two-dimensional pictorial programming. A big problem is that two-dimensional visual programming systems fail to manage a lot of pictorial programming elements. This paper proposes a new pragmatic three-dimensional visual programming system "3D-PP" to solve the problem.